Love, sex and robots : an introspection on human desire and its moral significance on posthumanist views on biological liberation - Ng, Sonya (Nanyang Technological University, 2020)
This paper intends to examine the nature of sexual desire, and our ability to be free from, or in control of it. I intend to argue that our execution of sexual desire is a mixture of autonomous and heteronomous freedom that are ultimately a response and interaction with various sociological forces.